Strategi Konten Instagram untuk Edukasi Pola Minum Kopi yang Sehat pada Usia Muda - Muhammad Alvian Hasby; Erik Armayuda; Bayyinah Nurrul Haq (Universitas Persada Indonesia YAI, 2020)
Based on a survey conducted by the author in 2020, the intensity of drinking coffee at a youngage is quite high. They consume an average of 1-3 cups of coffee per day. One reason is the lackof information on the dangers of drinking excessive coffee. Therefore, it is necessary to design aneducational media regarding the dangers of drinking excessive coffee that reaches youngaudiences. The design of this educational media aims to provide knowledge about healthydrinking patterns. The preliminary research was carried out through survey methods andliterature studies. The social media platform used is Instagram with the microblog concept. Thetarget audience is between 20-30 years old and in the Jabodetabek area who likes to interact viasocial media. Media design visually displays a warm, comfortable, and pleasant impressionthrough color, visual elements in the form of photos and vectors. Design verbally (how to say)through light language and bring a relaxed, comfortable, and familiar atmosphere. The verbaldelivery strategy uses light, relaxed, and familiar language. Information is conveyed in stagesand varied, namely: facts about coffee, the dangerous risks of drinking excessive coffee, andhealthy drinking patterns. Platform-related content management through the use of trending andrelevant hashtags, posting arrangements that refer to the educational cycle resulting in a schedulefor posting content that is divided into several editions for one month.